Potential growth prospects: Risks, rewards, and policies - Sinem Kılıç Çelik; M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
Potential output growth around the world slowed over the past two decades. This slowdown is expected to continue in the remainder of the 2020s: global potential growth is projected to average 2.2 percent per year in 2022-30, 0.4 percentage point below its 2011-21 average. Emerging market and developing economies (EMDEs) will face an even steeper slowdown, of about 1.0 percentage point to 4.0 percent per year on average during 2022-30. The slowdown will be widespread, affecting most EMDEs and countries accounting for 70 percent of global GDP. Global potential growth over the remainder of this decade could be even slower than projected in the baseline scenario - by another 0.2-0.9 percentage point a year - if investment growth, improvements in health and education outcomes, or developments in labor markets disappoint, or if adverse events materialize. A menu of policy options is available to help reverse the trend of weakening economic growth, including policies to enhance physical and human capital accumulation; to encourage labor force participation by women and older adults; to improve the efficiency of public spending; and to mitigate and adapt to climate change, including infrastructure investment to facilitate the green transition.
Keywords: E30; E32; E37; O20; 330; production function; growth expectations; emerging markets; developing economies